Analysis of Fungi in the Respiratory Tract of Patients with Tuberculosis at the Palembang Public Health Laboratory Center (BBLKM Palembang) - Herry Hermansyah; Sri Sulpha Siregar; Erwin Edyansyah (Jurnal Teknologi Laboratorium)
Tuberculosis (TB) is a contagious disease caused by Mycobacterium tuberculosis that most often affects the lungs. It is classified as an airborne disease since it spreads through the air when people with TB cough, sneeze, or spit. Indonesia is one of the countries with the total high TB burden worldwide. The estimated number of people who fell ill because of TB reached 845,000, with a death rate of 98,000, or equivalent to 11 deaths/hour. The control of TB in Indonesia has been carried out for more than seventy years, but Indonesia is still reported as the country with the second-highest TB burden in the world. The long-term use of anti-TB drugs or Multidrug-resistant TB (MDR-TB), an immunosuppressive agent, can cause fungal infections. Fungal infections can occur in the earlier stage of the disease, but the patients are only given anti-TB drugs. It takes longer for them to recover due to fungal coinfections. The purpose of this study was to find out the frequency distribution of tuberculosis based on the characteristics of patients (age, gender, and type of fungi) and to investigate the statistical distribution of fungi based on the characteristics of sputum i.e color (mucopurulent), consistency (viscosity), and blood presence (hemoptysis). This study used an analytical research design with an observational cross-sectional approach. The samples of this study were sputum taken from 98 patients collected using an accidental sampling technique. The results of the study revealed that, of 98 patients, 81 (82.7%) were adult, 63 (64.3%) were male, 41 (41.9%) were infected with Candida sp, 9 (9.1%) with Aspergillus sp, and 17 (17.3%) with mixed infection. Meanwhile, 31 (31.7%) samples were found negative. In addition, there was no significant relationship between the types of fungi and the characteristics of sputum.